ANALISIS NOVEL SUTI KARYA SAPARDI DJOKO DAMONO DITINJAU DARI ASPEK SOSIOLOGI SASTRA - Malo Marta Yeni; I Nyoman Suparsa; Ni Wayan Eminda Sari (Prodi Pendidikan Bahasa dan Sastra Indonesia FKIP Unmas Denpasar, 2023)
This research is a descriptive research that aims to gain an understanding of the social and cultural aspects. Data collection uses the method of observation and documentation. The data obtained were analyzed by descriptive qualitative. The social aspect is a major part of human life. In everyday life, every human being carries out social processes on an ongoing basis. As is the case in a story in a literary work, there are various kinds of social aspects including cooperation, competition and conflict. This process occurs in various domains, be it in the realm of friends, family and society. In the cultural aspect, it is an aspect that examines a culture or habits of the people that exist on the surface of the earth such as kinship, love, religion and education. Sociological research on this literary work discusses social and cultural aspects in the novel Suti by Sapardi Djoko Damono. To be able to understand the social and cultural aspects that occur between characters, the researcher analyzes it using the study of sociology of literary works. Researchers can conclude that the novel Suti by Sapardi Djoko Damono describes the social and cultural aspects that intertwine between characters. These social and cultural aspects are not only experienced by Suti as the main character, but also by other figures. The social and cultural aspects found in Suti's novel consist of cooperation, competition, conflict, kinship, love, religion and education.